Psychological dynamics of performance (1998)
This fifth issue of Volume 3 of Coaching Science Abstracts reviews 32 articles concerned with psychological dynamics and mental content that affects performance. The variety of sub-topics indicates only a few of the complexity of factors that govern performance outcomes in training and competitive settings. Sub-Topics: - TEAM BUILDING, - STRATEGIES, - PSYCHING-UP, - PSYCHOLOGICAL SKILLS TRAINING, - COMPETITION THINKING.